ANALISIS STRATEGI PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN ORANG PRIBADI SECARA MANUAL DI ERA DIGITAL PADA KANTOR PELAYANAN PAJAK PRATAMA JAKARTA PESANGGRAHAN PERIODE 2022 SAMPAI DENGAN 2024 - Dian Wahyudin; Fajar Ardian Sinatriya (Jurnal Ilmu Administrasi Publik, 2026)
This study aims to analyze the manual submission of Individual Annual Tax Returns (SPT) amidst the massive digitalization of taxation at the Jakarta Pesanggrahan Small Tax Office (KPP Pratama) for the 2022-2024 period. The research method used is qualitative, with data collection through in-depth interviews and documentation. Data analysis was conducted using the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats) to evaluate the organization's internal and external factors. The results show that KPP Pratama Jakarta Pesanggrahan has a positive and appreciative perception of manual Taxpayers, who are predominantly elderly individuals and newly registered Taxpayers. The main challenges faced include the administration process of manually reported Individual Annual Tax Returns, which must go through scanning and physical archiving, as well as data validity issues in Tax Returns sent via mail. The strategies implemented by the institution include optimizing Helpdesk services during peak season and educational programs through Pojok Pajak at the urban village (Kelurahan) level. The study concludes that there is a need for simpler visual education for elderly Taxpayers to encourage a sustainable transition to the digital system. Keywords Annual Tax Return, Manual Reporting, Taxation Digitalization